Knowledge construction and systematization of solar adsorption refrigeration prototypes. (November 2021) - Alvarez, José C.; Bravo, Leonardo; Marçal, Roberto C.; Hatakeyama, Kazuo; Barrantes, Enrique
Abstract: Tests of adsorption cooling prototypes with solar energy that use the silica gel–water​ pair have been reported in the literature; however, there is no work that analyzes, compares and integrates them to generate new knowledge from their data and results. In this context, our proposal consists comparing thermodynamic results, determining the characteristics of their parts and functions, and analyzing technical contradictions through the TRIZ methodology, for twelve identified adsorption refrigeration prototypes (including one where a co-author of this paper participated). The results and characteristics of the analyzed prototypes have been systematized, also a diversity of constructive forms was found in the studied prototypes, as well as in the non-standardized results and tests because some aspects were emphasized in each test. The results and simulations are compared using COP and refrigeration capacity as parameters to extrapolate new results consisting of a hybridized conceptual model and projected test results based on those found in the literature.